2021
DOI: 10.1186/s12891-021-04470-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gluteus medius strength between individuals with obesity and normal-weight individuals: a cross-sectional study

Abstract: Background The hip abductor muscles, primarily the gluteus medius, play an important role in stabilizing the pelvis during gait. Gluteus medius weakness is associated with biomechanical changes and musculoskeletal disorders. Individuals with obesity can have great difficulty maintaining abductor muscular function due to being overweight and possibly experiencing a decrease in muscle mass. However, it is still unclear whether the musculature of person with obesity can compensate for these change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…However, the increased CoP path length in this study also suggests that obese young male adults could have an unbalance in muscle strength between the adductor and abductor muscles, influencing their postural control in ML direction during GI. The reason for this finding is that dynamic postural balance control needs appropriate intensity muscle contractions of all proximal muscles of the lower limbs during walking, but obese individuals have a relative weakness in the specific contractile performance and quality of hip abductor muscles (Fenato et al, 2021), like gluteus medius, compared with normal-weight ones. The partial lower extremity muscle over-contraction destabilizes the overall body frame and increases the challenge of maintaining postural control in the frontal plane for obese individuals.…”
Section: Influence Of Excess Weight On Young Male Adults' Cop Parametersmentioning
confidence: 99%
“…However, the increased CoP path length in this study also suggests that obese young male adults could have an unbalance in muscle strength between the adductor and abductor muscles, influencing their postural control in ML direction during GI. The reason for this finding is that dynamic postural balance control needs appropriate intensity muscle contractions of all proximal muscles of the lower limbs during walking, but obese individuals have a relative weakness in the specific contractile performance and quality of hip abductor muscles (Fenato et al, 2021), like gluteus medius, compared with normal-weight ones. The partial lower extremity muscle over-contraction destabilizes the overall body frame and increases the challenge of maintaining postural control in the frontal plane for obese individuals.…”
Section: Influence Of Excess Weight On Young Male Adults' Cop Parametersmentioning
confidence: 99%
“… 13 Another latest study by Fenato RR found the relation of gluteus medius muscle strength with obesity and normal weight. 20 In the current study BMI was calculated for each participant, but no correlation of BMI was explored with the muscle strength assessed.…”
Section: Discussionmentioning
confidence: 99%